Phase-controllable growth of ultrathin 2D magnetic FeTe crystals - Kang, Lixing (2021)
Two-dimensional (2D) magnets with intrinsic ferromagnetic/antiferromagnetic (FM/AFM) ordering are highly desirable for future spintronic devices. However, the direct growth of their crystals is in its infancy. Here we report a chemical vapor deposition approach to controllably grow layered tetragonal and non-layered hexagonal FeTe nanoplates with their thicknesses down to 3.6 and 2.8 nm, respectively. Moreover, transport measurements reveal these obtained FeTe nanoflakes show a thickness-dependent magnetic transition. Antiferromagnetic tetragonal FeTe with the Néel temperature (TN) gradually decreases from 70 to 45 K as the thickness declines from 32 to 5 nm. And ferromagnetic hexagonal FeTe is accompanied by a drop of the Curie temperature (TC) from 220 K (30 nm) to 170 K (4 nm). Theoretical calculations indicate that the ferromagnetic order in hexagonal FeTe is originated from its concomitant lattice distortion and Stoner instability. This study highlights its potential applications in future spintronic devices.